Finance, & Marketing Distribusi di sebuah Produksi Film - RR Ella Evrita H, S. E, M.M, RR Ella Evrita H, S. E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
Financing of film projects often requires an elaborate patchwork of investors, banks, soft money tax credits and in-kind services, and some companies specialize in financing specific stages of production. One of the overall themes of the industry that can at times make obtaining financing hard is the risks involved in making films, many of which may have very little tangible value at the end of the process. How an independent filmmaker chooses to make a movie is often dictated by access to money more than any aesthetic sensibilities. Without the proper funding, a feature film never gets made or made the way the filmmaker wants to. Which strategy the filmmaker uses to access funding will depend on the type of film, the story or subject matter, the budget, genre, the filmmaker’s reputation, the talent attached and the amount of creative control the filmmaker wants over the production.